KINETICS AND MECHANISM OF PHOTODEGRADATION OF CHLOROPHENOLS. (1st March 1998) - Burrows, Hugh; Ernestova, Ludmila; Kemp, Terence; Skurlatov, Yuri; Purmal, Anatol; Yermakov, Alexander
The photodegradation of mono-, di-, tri- and pentachlorophenols in aqueous solution is surveyed from several viewpoints, namely kinetic and mechanistic, the nature of the reactive intermediates and final products, and the potential of photochemical means of treating water contaminated by chlorophenols. In direct photolysis, the roles of heterolytic and homolytic processes are considered, and the appearance of carbene, in addition to ionic and radical, intermediates noted. Sensitized photolysis deals with the roles of singlet oxygen and of a variety of metal complexes. The induced degradation of chlorophenols refers to the oxidation of chlorophenols by free radicals generated from photo- and radiolytic systems, particularly illuminated semiconductors such as titanium dioxide. The article finishes with an overview of the reactions of various types of reactive intermediates with chlorophenols.